Early adolescents’ use of information and communication technologies (ICTs) for social communication in 20 countriesExamining the roles of ICT-related behavioral and motivational characteristics - Areepattamannil, S.; Khine, Myint Swe (Elsevier, 2017)
Social interaction is integral to the healthy psychosocial development of adolescents. The rapid expansion and evolution of the Information and Communication Technology (ICT) sector over the last two decades has opened up a new world of unlimited opportunities and possibilities for social interaction. Despite the tremendous strides that have been made in the ICT sector, there has been a dearth of research on the factors linked to adolescents’ use of ICT for social interaction. The present study, therefore, drawing on data from the 2013 International Computer and Information Literacy Study (ICILS) database and employing three-level hierarchical linear modeling (HLM) as an analytic strategy, examined the predictive effects of ICT-related behavioral and motivational characteristics on the frequency of use of ICT for social communication among 56209 early adolescents from 3132 schools in 20 ICLIS participating countries. The results of the three-level HLM analyses, after accounting for student-, school-, and country-level demographic characteristics, revealed that early adolescents’ ICT-related behavioral and motivational characteristics significantly and positively predicted their use of ICT for social communication. Specifically, Internet access at home, number of computers at home, learning of ICT tasks at school, use of specific ICT applications, use of ICT during lessons at school, use of ICT for recreation, ICT self-efficacy, and interest as well as enjoyment in using ICT significantly and positively predicted the use of ICT for social communication among early adolescents in 20 countries. Implications of the findings are discussed briefly for policy and practice.